Utilization of Syif'ar Dental Tools in Learning The Introduction of Dental Tools to The Skill of Identifying Tools - Amaliah Asy-syifa (Journal Research of Social Science, Economics, and Management, 2022)
The dental health department is a vocational education that produces skilled graduates, so that in the learning process it requires strategies and methods that lead to practice to hone student skills by utilizing information technology. One of the effectiveness in learning can be done using the development of learning media through Augmented Reality technology. Produce the SYIF'AR Dental Tools model as a learning media for the skill of identifying tools. This type of research is a mix method, which is a combination of qualitative and quantitative approaches in producing products. The research collected data with descriptive methods while testing the effectiveness of the product with analytical methods. This research design is Research and Development. The research subjects were 2 groups: Intervention 40 people and Control 40 people. Test data using Wilcoxon and Mann-Whitney. The feasibility test of SYIF 'AR Dental Tools in learning the introduction of dental tools obtained 91% (very feasible). Test the effectiveness of the skill of identifying tools with a p-value of 0.000 (effective). The results of the effectiveness test of unpaired data change value ? 26.73 and p value of 0.000 (effective). Augmented reality technology has been made whose application is feasible and effective on the skills of identifying tools in learning the introduction of dental tools in students. The use of augmented reality technology is more effective than the use of printed books.